Potential Neuroprotective Role of Sugammadex: A Clinical Study on Cognitive Function Assessment in an Enhanced Recovery After Cardiac Surgery Approach and an Experimental Study - Muedra, Vicente; Rodilla, Vicent; Llansola, Marta; Agustí, Ana; Pla, Clara; Canto, Antolín; Hernández-Rabaza, Vicente (Frontiers in Cellular Neuroscience, 2022)
Background: Postoperative cognitive dysfunction affects the quality of recovery, particularly affecting the elderly, and poses a burden on the health system. We hypothesize that the use of sugammadex (SG) could optimize the quality of postoperative cognitive function and overall recovery through a neuroprotective effect. Methods: A pilot observational study in patients undergoing cardiac surgery with Enhanced Recovery After Surgery (ERAS), was designed to compare Sugammadex-treated (SG, n=14) vs. neostigmine-treated (NG, n=7) patients. The Postoperative Quality Recovery Scale (PORS) was used at different times to evaluate patients’ cognitive function and overall recovery. An online survey amongst anesthesiologists on SG use was also performed. Additionally, an animal model study was designed to explore the SG effects on the hippocampus. Results: SG was associated with favorable postoperative recovery in cognitive domains particularly 30 days after surgery in patients undergoing aortic valve replacement by cardiopulmonary bypass and ERACS approach; however, it failed to demonstrate a short-term decrease in length of ICU and hospital stay. The survey information indicated a positive appreciation of the SG recovery properties. The SG reverts postoperative memory deficit and induces the expression of anti-inflammatory microglial markers. Conclusions: The results show a postoperative cognitive improvement by SG treatment in patients undergoing aortic valve replacement procedure by ERACS approach. Additionally, experimental data from an animal model of mild surgery, confirm the cognitive SG effect and suggest a potential effect over glia cells as an underlying mechanism.